2020
DOI: 10.6023/cjoc202006034
|View full text |Cite
|
Sign up to set email alerts
|

Four New 2-Pyrones from Fusarium tricinctum, an Endophytic Fungus of Ligusticum chuanxiong

Abstract: By silica gel, Sephadex LH-20 column chromatography as well as preparative high performance liquid chromatography (HPLC), four previously undescribed α-pyrones sharing same primary structure were isolated from the brown rice solid medium of Fusarium tricinctum. Their structures were elucidated by spectroscopic analyses and their absolute configurations were finally confirmed by a modified Snatzke's method. Keywords 2-pyrone; Fusarium tricinctum; Ligusticum chuanxiong; induced circular dichroism Results and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…CD comparison showed that the absolute configurations of the chiral carbons in the tetrahydrofuran moiety of 6 are 5 S , 6 R , and 7 S . As the Mo 2 -erythro-vic-diols complex can generate two favored conformations, which can cause opposite optical rotations, Cotton effects produced by the Mo 2 -threo-vic-diols complex should be stronger than those yielded by the Mo 2 -erythro-vic-diols complex when samples are measured at the same concentration . Herein, the ICD spectra of both 5 and 6 show negative signs at bands II and IV, clarifying the absolute configurations of the two compounds.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…CD comparison showed that the absolute configurations of the chiral carbons in the tetrahydrofuran moiety of 6 are 5 S , 6 R , and 7 S . As the Mo 2 -erythro-vic-diols complex can generate two favored conformations, which can cause opposite optical rotations, Cotton effects produced by the Mo 2 -threo-vic-diols complex should be stronger than those yielded by the Mo 2 -erythro-vic-diols complex when samples are measured at the same concentration . Herein, the ICD spectra of both 5 and 6 show negative signs at bands II and IV, clarifying the absolute configurations of the two compounds.…”
Section: Resultsmentioning
confidence: 62%
“…In 9 , the chemical shifts of C-1′ (Δ δ = +2.4 ppm), C-3′ (Δ δ = +4.6 ppm), and C-5′ (Δ δ = +4.9 ppm) are significantly deshielded, and those of C-2′ (Δ δ = −5.1 ppm) and C-4′ (Δ δ = −3.0 ppm) are shielded. Therefore, 9 was deduced to be an epimer of globosumone C. As the relative configurations of the vic-diol group in globosumone C is erythro, the relative configurations of hydroxy groups at positions 3′ and 4′ in 9 were deduced as threo. The ICD spectrum (Figure ) of 9 shows negative Cotton effects at bands II and IV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation